An approach on the use of predictive microbiology for biofilm formation (Research, Society and Development, 2020)
It is necessary to ensure food quality and safety during all stages of food production. The major challenge in the food sector is the control of microbial multiplication, as microorganisms are increasingly looking for alternatives, which involve their development, both in free form as in biofilm, to survive environmental attacks. Due to this concern, researchers use new strategies to understand the dynamics of microbial growth. In this context, predictive microbiology is gaining space in food microbiology. Therefore, the objective of the study was to verify whether the current predictive models are adequate to predict the growth of sessile cells, as well as planktonic cells. A bibliographic survey on the application of predictive microbiology in the evaluation of food safety control was carried out, and we concluded that, due to the scarcity of studies, it was not possible to state the adequacy of tertiary models in the control of biofilms during food production. We highlight the need for studies that can model the formation of biofilm of pathogens under different environmental factors.